The independent role of fine particulate matter and genetic liability on cognition in older adults - Shu-Fen Liao; Ta-Chien Chan; Mei-Hsin Su; Mei-Chen Lin; Chi-Shin Wu; Chun-Chieh Fan; Shi-Heng Wang (Annals of General Psychiatry)
Abstract Background Genetic susceptibility to mental health and cognitive traits, as well as air pollution, significantly impact cognition. The interplay between polygenic liability and fine particulate matter (PM2.5) remains unclear due to the limited number of large-scale studies in Asia. This study utilized the Taiwan Biobank, a nationwide community-based database, to investigate the main and modified effect of PM2.5 on individuals’ polygenic susceptibility in cognition. Methods Polygenic risk score (PRS) for cognitive performance (CP PRS), Alzheimer’s disease (AD PRS), schizophrenia (SCZ PRS), and major depression (MDD PRS) were computed representing genetic susceptibility for an individual. APOE genotype was classified into E3/E3, E3/E4, and E4/E4. The five-year average concentration of PM2.5 from satellite images was used for defining environmental exposure. Cognitive performance was evaluated via the Mini-Mental State Examination (MMSE) score. The association between personal genetic susceptibility, PM2.5, and cognitive performance was examined using multilevel linear regression with the adjustment of age, sex, batch effect, and population stratification effect. The gene-environment synergism was examined with the inclusion of product term of PM2.5 and PRS in the multivariate model. Results Our analyses included 25,593 participants from 164 townships. Participants exposed to higher PM2.5 concentrations had a lower MMSE score (Beta=-0.0830 corresponding to a 1 µg/m3 increase in PM2.5 concentration, 95% CI, -0.0973 to -0.0688, p-value < 0.0001). After controlling for PM2.5 concentration, CP PRS (Beta = 0.1729, 95% CI, 0.1470 to 0.1988, p-value < 0.0001), SCZ PRS (Beta=-0.0632, 95% CI, -0.0891 to -0.0374, p-value < 0.0001), and AD PRS (Beta=-0.0321, 95% CI, -0.0580 to -0.0062, p-value = 0.0153) were associated with MMSE score. After further examination of gene-environment synergism, no interaction effect was identified, indicating different mechanism of PM2.5 and genetic liability to influence cognitive performance. Conclusions Human polygenic loading and PM2.5 may impact cognition via an independent pathway. A prevention strategy targeting air pollution reduction may effectively improve the cognitive performance. Multiple exposures and their influences on the long-term change of cognition were required in future research.